Performance measurement system using performance prism approach in batik company: a case study - Vembri Noor Helia; Wahyudhi Sutrisno; Afriza Syawal Zaputra; Qurtubi Qurtubi (Jurnal Sistem dan Manajemen Industri, 2021)
XYZ company is one of the small-medium enterprises (SME) engaged in the batik industry with the main focus on making muslim clothes made from printed batik and batik. The company cannot evaluate the cause of the turnover decrease because no performance measurement has been applied. Therefore, a company performance measurement is carried out using the performance prism approach because a company performance appraisal is needed stakeholder contributions using the performance prism approach. Stakeholders of this company are consumers, employees, community, capital owners, and suppliers. Supporting the performance prism framework, the AHP method was used to determine the weighting and hierarchical structure and then carried out a scoring system with the help of OMAX to determine the company's actual score. This design shows that corporate stakeholders, including owners, consumers, employees, suppliers, and the surrounding community, obtained as many as 34 KPIs. From the implementation of the performance measurement system with OMAX scoring obtained the value of company performance based on satisfaction aspects (6.489), contribution aspect (6.582), and capability aspect (5.646). Recommendations are also given to improve it.